2016
DOI: 10.1016/j.jacc.2015.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Does Vascular Calcification Accelerate Inflammation?

Abstract: Across multiple arterial regions, higher age is consistently associated with higher calcium scores. The presence of vascular calcification at baseline is associated with progressive calcification; in the carotid arteries, calcification appears to influence vascular inflammation. Dalcetrapib therapy did not affect vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 39 publications
2
39
1
1
Order By: Relevance
“…In the PROSPECT trial, patients with the highest calcium volumes had the worst outcomes . However, while calcification in other vascular beds has not been extensively studied, age > 65 years was consistently associated with higher baseline arterial calcification in the carotid and coronary arteries and aortic arch . In our study, the circumferential distribution of calcification was similar among all PAD beds (154–210°), but the absolute length of calcium was longest in the iliac/femoropopliteal arteries and shortest in the renal arteries.…”
Section: Discussionmentioning
confidence: 44%
“…In the PROSPECT trial, patients with the highest calcium volumes had the worst outcomes . However, while calcification in other vascular beds has not been extensively studied, age > 65 years was consistently associated with higher baseline arterial calcification in the carotid and coronary arteries and aortic arch . In our study, the circumferential distribution of calcification was similar among all PAD beds (154–210°), but the absolute length of calcium was longest in the iliac/femoropopliteal arteries and shortest in the renal arteries.…”
Section: Discussionmentioning
confidence: 44%
“…The inhibition of Rb has also been linked to increases in atherosclerotic lesion size as well as smooth muscle cell proliferation 27. Furthermore, inflammation has been postulated as a common pathway of viral‐mediated injury and atherosclerosis 25, 28. Caspases, which are protein enzymes that are vital to the process of vascular inflammation and cellular apoptosis, have been linked with the development of atherosclerosis, and recent reports have suggested that HPV E6 oncoproteins may promote nuclear localization of active caspase 8, leading to increased inflammation and probable atherosclerosis 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite crystals in the vessel wall share histological findings with ectopically formed bone (eg, the presence of osteoclast‐like and osteoblast‐like cells) 94. Early pathologic studies also observed that arterial calcification resembles a focus of skeleton‐like tissue 95.…”
Section: Positron Emission Tomographymentioning
confidence: 99%